Children television viewing and antisocial behavior: does the duration of exposure matter? - Nazari, Mohammad Reza; Hassan, Md Salleh; Osman, Mohd Nizam; Parhizkar, Saadat; Yasin, Megat Al-Imran (Macrothink Institute, 2013)
Media violence is related to media presentation of aggressive and violent behaviour directed at characters in the media story. Specifically, researchers have identified evidence that children's exposure to television violence is directly related to immediate and later aggressive behaviour. The relationship between television exposure and students; aggression behavior has not been studied extensively in Iranian elementary students. The purpose of this study was to assess the relative effects of television exposure on aggression behaviour among elementary students in Iran.A cross-sectional survey was conducted on 424 primary school students (aged 7-12 years) in the five provinces of Iran which selected trough a multi-stage random sampling from different geographical areas comprising of North, South, West, East and central area of Iran. This survey investigated whether exposure to television program was related to children's use of social aggression that explored using Buss- Perry standard questionnaire. The results of the study revealed a significant relationship between amount of exposure to television program and aggressive behaviours among primary school students (p<0.05). In addition, students’ aggression was positively associated with watching movies with action genre (p<0.05). Furthermore students’ leisure time filling with television was moderately correlated with their aggression level. The findings suggest that young people’s aggressive behaviours may be related to their frequent exposure to television programs and its violent contents. Results of this study suggested the need for further attention on television children’s program production to protect them from antisocial behaviours and interventions for violence-exposed children in order to reduce negative outcomes.